2022
DOI: 10.3233/prm-200689
|View full text |Cite
|
Sign up to set email alerts
|

Is self-image, in reference to the gravitational vertical, altered in adolescent idiopathic scoliosis? A multicenter, single-blind, case-control study

Abstract: PURPOSE: Adolescent idiopathic scoliosis (AIS) is associated with perturbation of orthostatic postural control. In humans, orthostatic postural control is organized around the gravitational vertical (GV). Perception of the GV involves a bottom-up process (central integration of multisensorial information) and a top-down process that uses cognitive mechanisms relying on body image. This study hypothesized that AIS would be associated with an erroneous central representation of verticality. The objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Recently, a review found that IS subjects appear to show structural abnormalities of the vestibular apparatus 8 . This could compromise the perception of the subject's gravitational verticality 44 and cause an alteration of self‐image 51 . These works have speculated that spinal curvature could develop in response to an inappropriate postural pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a review found that IS subjects appear to show structural abnormalities of the vestibular apparatus 8 . This could compromise the perception of the subject's gravitational verticality 44 and cause an alteration of self‐image 51 . These works have speculated that spinal curvature could develop in response to an inappropriate postural pattern.…”
Section: Discussionmentioning
confidence: 99%
“…8 This could compromise the perception of the subject's gravitational verticality 44 and cause an alteration of self-image. 51 These works have speculated that spinal curvature could develop in response to an inappropriate postural pattern. Although the alteration of the perception of visual verticality in subjects with IS is not completely clear, 15 the distortion of the perception of verticality could cause coronal head tilt, 52 and it does seem that the treatment of a spinal curvature through exercises could destabilize the subject's internal schema, producing a deviation from the subjective visual vertical.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The second run epoch is identical to the first. The rats’ position is tracked by an overhead camera and liquid rewards are automatically delivered (Peira bvba, Belgium) based on the tracked behavior using custom developed software in the lab ( Catanzariti et al, 2022 ; https://bitbucket.org/kloostermannerflab/fklab-controller-lab copy archived at KloostermanNERFLab, 2024 ).…”
Section: Methodsmentioning
confidence: 99%